"Oh, My God, I Hate You:" The Felt Experience of Being Othered for Being Thin. Issue 3 (17th June 2015) - Beggan, James K.; DeAngelis, Mattie
<x xml:space="preserve">Abstract</x> It is universally held among researchers and social critics that a thin ideal dominates current cultural conceptions of what is attractive, especially for women. Using interviews with eighteen women and men, this paper investigates an apparent paradox: how thin people negotiate a landscape where the attention they receive because of their thinness distresses them. Results indicate that thin people are often the target of unwanted comments about their size, comments produce an unpleasant state of self‐consciousness, and the expectation of unwanted social interaction will motivate thin individuals to avoid certain social situations. Results are interpreted in terms of thinness being a hypervisible condition that produces a breakdown of norms regarding civil inattention toward thinness and produces the experience of being othered by social perceivers.